Hubungan Konten Parenting Islami dengan Gaya Parenting Pasangan Muda: Studi Kasus Pada Orang Tua Pengguna Instagram - Setiani, Mefta; Wahyuni, Citra; Firma, Try Bunga; Savitri, Shalsa; Fidaus, Muhamad Yoga (Jurnal Penelitian Ilmu Ushuluddin, 2022)
This study aims to discuss the relationship of Islamic parenting content on Instagram social media to the parenting style of young couples in Indonesia. The subjects in this study were 10 parents with the following criteria: age of marriage under 10 years; already have children; actively use Instagram; and follow Islamic parenting accounts on Instagram. The research instrument used is a questionnaire sheet consisting of two parts, namely the parenting style questionnaire and the questionnaire related to Islamic parenting content on Instagram. This study uses a descriptive quantitative approach, where respondents' answers are described and linked to a literature review. The results of this study are 2 respondents are in the category of high Islamic parenting understanding, 8 respondents have low Islamic parenting understanding. Meanwhile, for parenting style, 3 respondents have authoritarian parenting style, 3 respondents have authoritative parenting style, and 4 respondents have permissive parenting style. Based on the results of the chi-square test using spss, it is known that the Asimpsig value is 0.153>0.05, it can be concluded that there is no significant relationship between understanding Islamic parenting content and parenting style. This can also mean that the respondents' understanding of Islamic parenting content has no correlation with parenting style.